2011
DOI: 10.1007/s11071-011-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

A model reference robust multiple-surfaces design for tracking control of radial pneumatic motion systems

Abstract: A robust model reference backstepping (multiple-surfaces) controller is proposed for radial pneumatic motor motion systems with variable inlet pressure and mismatched uncertainties (time-varying payload). A radial pneumatic motor is first modeled by a non-autonomous equation with consideration of a ball screw table. A practical integral action and robust action are included in the backstepping design to compensate for the disturbance, mismatched uncertainty, and to eliminate the steady state error. The motion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Many industrial applications such as those requiring manipulators, riveting machines, automobiles, pick-and-place devices, and others have made extensive use of pneumatic actuators. This is because pneumatic systems have a variety of benefits, including ease of maintenance, lower cost, low heat under steady load and many others [1][2][3]. The pneumatic actuator continues to garner ever more research interest as a result of these benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Many industrial applications such as those requiring manipulators, riveting machines, automobiles, pick-and-place devices, and others have made extensive use of pneumatic actuators. This is because pneumatic systems have a variety of benefits, including ease of maintenance, lower cost, low heat under steady load and many others [1][2][3]. The pneumatic actuator continues to garner ever more research interest as a result of these benefits.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve expected control performance, a primary prerequisite for using this technique typically involves the knowledge or estimation of changes and bounds of system uncertain parameters. Recent studies regarding robust control of pneumatic actuating systems can be found in three primary groups: adaptive robust control, 1,2 sliding mode control, 36 and H ∞ control-related techniques. 714 To perform state feedback control based on a limited output measurement, deriving an accurate mathematical model or adding extra sensors is necessary for the first two methods.…”
Section: Introductionmentioning
confidence: 99%